HUBUNGAN ANTARA SELF-CONFIDENCE DAN SPEAKING SKILLS SISWA SEKOLAH DASAR: LITERATURE REVIEW - Alisah; Utami, Nidya Chandra Muji; Imaningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to gain a deeper understanding of the relationship between self-confidence and speaking skills in elementary school students through a literature review. The research uses a literature review method by collecting journal articles to be read and analyzed. Based on the findings of the literature study, it can be concluded that there is a significant relationship between self-confidence and speaking skills in elementary school students. An increase in self-confidence positively impacts the students' speaking ability, emphasizing the importance of developing self-confidence in the speaking learning process.